Autophagy-related lncRNAs and exosomal lncRNAs in colorectal cancer: focusing on lncRNA-targeted strategies - Yan Dong; Yiwei He; Yanna Geng; Meimei Wei; Xiaomei Zhou; Jianlun Lian; Jamal Hallajzadeh (Cancer Cell International, 2024)
Abstract Autophagy is a cellular process that involves the degradation and recycling of cellular components, including damaged proteins and organelles. It is an important mechanism for maintaining cellular homeostasis and has been implicated in various diseases, including cancer. Long non-coding RNAs (lncRNAs) are a class of RNA molecules that do not code for proteins but instead play regulatory roles in gene expression. Emerging evidence suggests that lncRNAs can influence autophagy and contribute to the development and progression of colorectal cancer (CRC). Several lncRNAs have been identified as key players in modulating autophagy in CRC. The dysregulation of autophagy and non-coding RNAs (ncRNAs) in CRC suggests a complex interplay between these two factors in the pathogenesis of the disease. Modulating autophagy may sensitize cancer cells to existing therapies or improve the efficacy of new treatment approaches. Additionally, targeting specific lncRNAs involved in autophagy regulation could potentially be used as a therapeutic intervention to inhibit tumor growth, metastasis, and overcome drug resistance in CRC. In this review, a thorough overview is presented, encompassing the functions and underlying mechanisms of autophagy-related lncRNAs in a range of critical areas within tumor biology. These include cell proliferation, apoptosis, migration, invasion, drug resistance, angiogenesis, and radiation resistance.